Ensuring inclusivity and well-being of refugee children in Malaysia through philanthropy / Dina Imam Supaat - Imam Supaat, Dina (2023)
Children who are refugees are seeking shelter in Malaysia owing to various forms of persecution, and they face particular difficulties in the host nation due to their restricted access to social inclusion, healthcare, and education. This study explores the critical function of philanthropic endeavours in promoting inclusivity and improving the wellbeing of refugee children in Malaysia, particularly through the provision of education. This is in line with the Sustainable Development Goals (SDGs). This qualitative study aims to analyse how philanthropic efforts in Malaysia have impacted the inclusion of refugee children and improved their well-being. The research methodology used involves desk and library research, drawing on a thorough examination of the existing literature, reports, and data relating to philanthropic intervention for refugee children in Malaysia. The analysis in this study is primarily descriptive and provides a comprehensive overview of philanthropic efforts made in support of refugee children. It explores the specific programs and initiatives undertaken by philanthropic organizations to address the multifaceted needs of this vulnerable population focusing on the realization of the right to education and the challenges they face. Findings of this study highlight the significant contributions of philanthropy in promoting the well-being and social inclusion of refugee children in Malaysia which are consistent with various SDGs. The research emphasises the importance of continued collaboration and ongoing cooperation to guarantee a brighter future for refugee children in Malaysia, regardless of their status.